Outbreak of measles in adults - Ristanović Ana (Association of Nurses Technicians and Midwives, 2016)
Morbilli is an acute infectious, viral, and highly contagious condition belonging to the group of rash-causing fever. Morbilli is caused by a virus from the family of Paramyxoviridae viruses (RNA). Clinical picture is dominated by three factors: fever, rash and cyclic course of the condition. Virus is present in rhyno pharyngeal secretions and tears, and it is placed in the group of droplet infections. Rash appears on the face and neck first, then it goes down the whole body. It disappears in the same way it develops. It is present in both small and large epidemies. It affects mostly children of pre-school and school age. Due to decreased immunity it can lead to many complications such as respiratory complications (bronchopneumonia, bronchiolitis and laryngitis), otorhinological complications (otitis, sinusitis), encephalitis. Last year in Bosnia and Herzegovina, that is in the Republic of Srpska, morbilli appeared. By following and analyzing the disease it is noticed that there is an impaired age structure of the patients suffering from morbilli. Hence, there is a need for constant refreshment of theoretical knowledge about the disease, in this case morbilli.